Exercise under heat stress: thermoregulation, hydration, performance implications and mitigation strategies - Periard, J. D.; Eijsvogels, T. M. H.; Daanen, H. A. M. (Physiological Reviews, 2021)
A rise in body core temperature and loss of body water via sweating are natural consequences of prolonged exercise in the heat. This review provides a comprehensive and integrative overview of how the human body responds to exercise under heat stress and the countermeasures that can be adopted to enhance aerobic performance under such environmental conditions. The fundamental concepts and physiological processes associated with thermoregulation and fluid balance are initially described, followed by a summary of methods to determine thermal strain and hydration status. An outline is provided on how exercise-heat stress disrupts these homeostatic processes, leading to hyperthermia, hypohydration, sodium disturbances and in some cases exertional heat illness. The impact of heat stress on human performance is also examined, including the underlying physiological mechanisms that mediate the impairment of exercise performance. Similarly, the influence of hydration status on performance in the heat and how systemic and peripheral hemodynamic adjustments contribute to fatigue development is elucidated. This review also discusses strategies to mitigate the effects of hyperthermia and hypohydration on exercise performance in the heat, by examining the benefits of heat acclimation, cooling strategies and hyperhydration. Finally, contemporary controversies are summarized and future research directions provided.